Discussion on Halal Assurance for Micro and Small Business: A Bibliometric and Content Analysis - Anita Priantina; Safeza Mohd Sapian; Devinna Pramitha; Aufa (Department of Management, Faculty of Economics and Management, University of Darussalam Gontor, Indonesia, 2024)
Non-Indexed Publication